2020
DOI: 10.1016/j.str.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the GNAT Fold in the Initiation of Polyketide Biosynthesis

Abstract: Highlights d GNAT superfamily catalyzes decarboxylation in addition to acyltransfer d A GNAT-like enzyme initiates biosynthesis of some polyketide natural products d Polyketide synthase GNAT-like enzymes catalyze only decarboxylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 67 publications
0
23
0
1
Order By: Relevance
“…Based on many studies of the chemical and kinetic mechanisms of GNAT enzymes, it is clear this superfamily has evolved to utilize a diversity of chemistries and active site residues for more complex and targeted modifications of acceptor substrates. Identification of additional non-acyl transfer reactions for GNATs, including decarboxylation, methylcarbamoyl transfer, and condensation ( Gu et al, 2007 ; Izoré et al, 2019 ; Karambelkar et al, 2020 ; Skiba et al, 2020 ) highlight the shear multitude of chemistries that enzymes from this superfamily can accomplish. Thus, GNATs appear to have a highly tunable scaffold that has evolved to modify a diverse range of substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on many studies of the chemical and kinetic mechanisms of GNAT enzymes, it is clear this superfamily has evolved to utilize a diversity of chemistries and active site residues for more complex and targeted modifications of acceptor substrates. Identification of additional non-acyl transfer reactions for GNATs, including decarboxylation, methylcarbamoyl transfer, and condensation ( Gu et al, 2007 ; Izoré et al, 2019 ; Karambelkar et al, 2020 ; Skiba et al, 2020 ) highlight the shear multitude of chemistries that enzymes from this superfamily can accomplish. Thus, GNATs appear to have a highly tunable scaffold that has evolved to modify a diverse range of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of GNATs that have been functionally characterized perform N- acetylation of primary amines ( Vetting et al, 2005b ; Favrot et al, 2016 ; Burckhardt and Escalante-Semerena, 2020 ), but a few examples of O- acetylation of hydroxyl groups exist ( Daigle et al, 1999 ; Hegde et al, 2001 ). Recent studies have also shown that the GNAT fold has been repurposed by some organisms to catalyze decarboxylation instead of acyl transfer, thus highlighting the sheer diversity of reaction capabilities of members of this superfamily of proteins ( Skiba et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In cis -AT modular PKSs, it is catalyzed by the N -terminal KS Q domain of PKSs 34 37 (Fig. 5a ), while in trans -AT modular PKSs, it is performed by a GCN5-related N -acetyltransferase (GNAT)-like domain 38 , 39 (Fig. 5b ).…”
Section: Discussionmentioning
confidence: 99%
“…Type C LM has a CoA-ligase domain rather than AT domain to incorporate carboxylic acid substrate in an ATP-dependent manner. Lastly, type D LM has a GCN5 N-acetyltransferaselike domain rather than AT domain that recently repurposed to catalyze decarboxylation (Skiba et al, 2020). A common characteristic of LMs is the absence of the condensation domain, which results a more flexible substrate specificity of the AT domain than those of downstream modules.…”
Section: Modular Pks and Nrps Architecture And Mechanismmentioning
confidence: 99%